2022
DOI: 10.3389/fmars.2022.1076804
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the bacterial community compositions of peanut worm (Sipunculus nudus) and their association with the surrounding environment

Abstract: The peanut worm (Sipunculus nudus) is an important economic and ecological fishery resource in China. To determine how S. nudus interacts with its culture environment, in this study, the diversity, composition, and interrelationships of bacterial communities in the intestine, coelomic fluid, and culture environment of S. nudus through high-throughput sequencing using the Illumina HiSeq sequencing platform. Alpha diversity analysis showed that the highest bacterial community richness and diversity were found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Li et al [ 7 ] analyzed the bacterial community composition of sediments from different layers in the S. nudus farming zone, and the bacterial community composition was changed by the bioturbation of S. nudus . Zhong et al [ 20 ] reported that Proteobacteria were the dominant bacterial communities in the intestine, coelomic fluid, and the culture environment of S. nudus , while the other dominant phyla were highly variable. The microbial communities in the intestine of S. nudus and three different surrounding sediments were analyzed by Li et al, and they found that the activity of S. nudus affected the bacterial community in sediments [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 7 ] analyzed the bacterial community composition of sediments from different layers in the S. nudus farming zone, and the bacterial community composition was changed by the bioturbation of S. nudus . Zhong et al [ 20 ] reported that Proteobacteria were the dominant bacterial communities in the intestine, coelomic fluid, and the culture environment of S. nudus , while the other dominant phyla were highly variable. The microbial communities in the intestine of S. nudus and three different surrounding sediments were analyzed by Li et al, and they found that the activity of S. nudus affected the bacterial community in sediments [ 21 ].…”
Section: Introductionmentioning
confidence: 99%